2002
DOI: 10.1002/neu.10070
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus and caudomedial neostriatum show selective responsiveness to conspecific song in the female zebra finch

Abstract: The perception of song is vital to the reproductive success of both male and female songbirds. Several neural structures underlying this perception have been identified by examining expression of immediate early genes (IEGs) following the presentation of conspecific or heterospecific song. In the few avian species investigated, areas outside of the circuit for song production contain neurons that are active following song presentation, specifically the caudal hyperstriatum ventrale (cHV) and caudomedial neostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 68 publications
6
89
0
Order By: Relevance
“…These areas are critical modulators of singing behavior (Nottebohm and Arnold, 1976) and song recognition (Mello et al, 1992;Chew et al, 1996;Bailey et al, 2002;Bailey and Wade, 2003). It is possible that synaptic aromatase may contribute to these processes in the zebra finch.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are critical modulators of singing behavior (Nottebohm and Arnold, 1976) and song recognition (Mello et al, 1992;Chew et al, 1996;Bailey et al, 2002;Bailey and Wade, 2003). It is possible that synaptic aromatase may contribute to these processes in the zebra finch.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, female zebra finches can learn to recognize songs to which they have been exposed, and they develop a preference for these songs (Riebel, 2000;Riebel et al, 2002). Several studies have shown that both the NCM and the CMHV are involved in processing conspecific songs in female songbirds (Chew et al, 1996;MacDougall-Shackleton et al, 1998;Duffy et al, 1999;Gentner et al, 2001;Bailey et al, 2002;Sockman et al, 2002;Bailey and Wade, 2003;Gentner and Margoliash, 2003;Grace et al, 2003;Maney et al, 2003;Phillmore et al, 2003), as well as in female budgerigars . Preliminary results from our own laboratory indicate that, in female zebra finches, the CMHV may be part of the neural representation of learned tutor song (Terpstra et al, 2001).…”
Section: The Role Of the Cmhv In Tutor Song Representationmentioning
confidence: 99%
“…All tissue was processed for c-fos immunohistochemistry in one run (as in Bailey et al, 2002;Wade, 2003, 2005). Briefly, after warming slides to room temperature, sections were rinsed, fixed in 4% paraformaldehyde and incubated in 0.5% hydrogen peroxide for 30 min followed by a 1-h incubation in 4% normal donkey serum in 0.1 M PBS with 0.3% Triton X-100.…”
Section: Immunohistochemistrymentioning
confidence: 99%